Discovery and Functional Evaluation of Antimicrobials - Kandasamy Saravanakumar; Kumar Vishven Naveen; Myeong-Hyeon Wang (Antibiotics, 2021)
Microbial infections pose a continuous threat to human health and healthcare systems around the globe [...]